2022
DOI: 10.3390/ani12121502
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Canine Mesenchymal Stem Cells Isolated from Different Sources

Abstract: In this study, we provide comprehensive analyses of mesenchymal stem cells (MSCs) isolated from three types of canine tissues: bone marrow (BM-MSCs), adipose tissue (AT-MSCs) and amniotic tissue (AM-MSCs). We compare their morphology, phenotype, multilineage potential and proliferation activity. The BM-MSCs and AM-MSCs showed fibroblast-like shapes against the spindle shape of the AT-MSCs. All populations showed strong osteogenic and chondrogenic potential. However, we observed phenotypic differences. The BM-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…MSCs are multipotent cells capable of differentiating into any type of body cell under suitable conditions [6]. The most common sources of MSC acquisition are adipose tissue (AT) and bone marrow (BM); however, these cells can also be obtained from tissues and organs such as skin, bone, dental pulp, liver, ovarian epithelium, and others [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are multipotent cells capable of differentiating into any type of body cell under suitable conditions [6]. The most common sources of MSC acquisition are adipose tissue (AT) and bone marrow (BM); however, these cells can also be obtained from tissues and organs such as skin, bone, dental pulp, liver, ovarian epithelium, and others [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are mostly obtained from bone marrow and adipose tissue (Neupane et al 2008). However, these cells can also be obtained from a variety of sources, including skin, dental pulp, liver, ovarian epithelium, umbilical cord, placenta, and amniotic membrane (Kerkis et al 2006;Crisan et al 2008;Humenik et al 2022). Previous research has shown that amnion tissue is a rich source of multipotent stem cells (Park et al 2012;de Oliveira Pinheiro et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Its collection and retrieval do not add to an animal's stress or suffering, as it is no longer needed in routine veterinary procedures, and it would become biological waste. Therefore, the eld of regenerative medicine pays particular attention to this tissue source (Humenik et al 2022). MSCs have the ability to differentiate into mesodermal cells such chondrocytes, osteoblasts, and adipocytes(Ullah, Subbarao, and Rho 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Iacono et al [ 25 ], in their review, observed that, like reported in human and other animal species, also in dog MSCs derived from foetal fluid and adnexa may have an attraction compared to other established SCs in different clinical approaches, although more in vitro studies on their metabolism and clinical applications are needed to fully understand their properties and to establish the future clinical use in the treatment of various diseases. In this contest, Humenik et al [ 26 ] described the effective protocols for the isolation of MSCs from canine bone marrow, adipose tissue, and amnion membrane, showing differences in yield of isolation, morphology, phenotype, multilineage potential, and proliferation activity.…”
mentioning
confidence: 99%
“…While Humenik et al compared canine MSCs isolated from AT, BM, and amniotic membrane, Merlo et al compared equine ATMSCs and WJ (Wharton’s jelly) MSCs [ 26 ]. Due to the difficulties encountered by the practitioners in skin wound healing and the role of integrin in the reparative process, in this pilot study, the authors analyzed the effect of an α4β1 integrin agonist on cell adhesion of equine AT and WJ-derived MSCs and investigated their adhesion ability to GM18 incorporated poly L-lactic acid (PLLA) scaffolds.…”
mentioning
confidence: 99%